PENGARUH GAME EDUKATIF TERHADAP KEMAMPUAN LITERASI DAN NUMERASI PESERTA DIDIK TINGKAT SEKOLAH DASAR - Lailiatul Qomariah; Nadya Arini Atmaja; Imana Bellany Filianti; Syazwina Ramaita Awra S; Finandya Putri Hanifatun Nurrohmah; Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Literacy and numeracy are thinking activities that involve learning symbols and the language that expresses them orally or in writing. Data from PISA 2018 shows significant challenges in improving these capabilities in Indonesia. The research method used is an experimental approach by conducting a pretest and posttest. This method is used to study students in a subject using certain learning media. The purpose of making this journal is to find out how much influence education has on the literacy and numeracy skills of elementary school level students. The results of the research show that the use of literacy and numeracy games has a positive impact on students' literacy and numeracy skills. Learners who engage in literacy games show significant improvements in reading ability and text comprehension, while numeracy games help improve basic math skills such as addition, subtraction and problem solving. Apart from that, these games also increase students' learning motivation, making the learning process more fun and interactive. These results indicate that the integration of educational games in the curriculum can be an effective strategy for improving students' literacy and numeracy skills.